Reductions of Particulate Matter Emissions of a Diesel Engine Fueled with Oxygenated and Emulsion Fuels - Hazman, Abu Hassan; R., Mamat; Hagos, F. Y. (American Scientific Publishers, 2019)
Diesel engine technology may soon be phased out from the market unless particulate matter and NO x emissions are dealt as per the standard requirements. There have been efforts to reduce these emissions through fuel side modifications. The current study is an extension of these efforts where diesel and biodiesel blend are modified to emulsify and oxygenate through water and alcohol to reduce emissions from the exhaust. Six types of properties are tested and their influence on particulate matter was investigated. The oxygenated fuels are tested for their emission behaviors in a four-stroke, single cylinder, water cooled, and direct fuel injection engine evaluated at a speed of 1800 rpm with the engine load varied at 0%, 50% and 100%. The method of fuel oxygenation and their effect on the concentration of particulate, soluble organic fraction, dry soot and particulate morphology are discussed. The results have demonstrated a significant reduction in the emission of the concentration of particulate matter, soluble organic fraction and dry soot with an increase in the fraction ratio of palm oil biodiesel. Emulsion of fuel is convenient for fuel due to the secondary atomization consequent from the micro-explosion and droplet breakdown responsible for the reduction in PM emissions. The morphology of particulate matter demonstrates that emulsified fuel produces lower soot concentration compared to biodiesel blends and diesel. Notably, emulsified and biodiesel blends can be utilized as an alternative fuel for diesel to maintain cleaner operation at all operation conditions with reduced PM and NO x emissions.